Biolistic inoculation of plants with viroid nucleic acids - Matousek, J; Orctová, L; Steger, G; Riesner, D (Journal of virological methods, 2004)
Parameters for biolistic transfer of viroid nucleic acids using a Helios Gene Gun device were assayed. The main achievement of this method is high efficiency of inoculation with linear monomeric viroid cDNAs and RNAs. This greatly facilitates the study of mutated sequence variants, viroid libraries and mixed populations. The lower limits for efficient inoculation of monomeric cDNA fragments with the sequence of potato spindle tuber viroid (PSTVd) and native PSTVd RNA as detected 21 days p.i. are in the range of 50 ng and 200 pg per tomato plant, respectively. At a higher dose, i.e. 2 ng of native RNA per plant, biolistic transfer causes drastic stunting compared to conventional mechanical inoculation, which points to higher PSTVd titers after the biolistic transfer. Infection is readily achieved with exact length monomeric RNA transcripts having 5'-triphosphate and 3'-OH termini in amounts ranging from 2 to 20 ng per plant, suggesting no need for any supplementary modifications of ends or RNA circularization. The biolistic transfer is efficient for viroid "thermomutants", which exhibit low or no infectivity with conventional mechanical inoculation with Carborundum. The biolistic inoculation is also efficient for two other members of the Pospiviroidae family, hop stunt and hop latent viroid.
Keywords: Plant Diseases; RNA, Double-Stranded; Biolistics; dvouvláknová RNA; Solanum lycopersicum; biolistika; Viroids; RNA, Viral; viroidy; RNA virová; Solanum tuberosum; nemoci rostlin